Decision Making in the Reward and Punishment Variants of the Iowa Gambling Task: Evidence of “Foresight” or “Framing”? - Singh, Varsha; Khan, Azizuddin (Frontiers in Neuroscience, 2012)
Surface-level differences in the reward and punishment variants, specifically greater long-term decision making in the punishment variant of the Iowa Gambling Task (IGT) observed in previous studies led to the present comparison of long-term decision making in the two IGT variants (n = 320, male = 160). It was contended that risk-aversion triggered by a positive frame of the reward variant and risk seeking triggered by a negative frame of the punishment variant appears as long-term decision making in the two IGT variants. Apart from the frame of the variant as a within-subjects factor (variant type: reward and punishment), the order in which the frame was triggered (order type: reward–punishment or punishment–reward), and the four types of instructions that delineated motivation towards reward from that of punishment (reward, punishment, reward and punishment, and no-hint) were hypothesized to have an effect on foresighted decision making in the IGT. As expected, long-term decision making differed across the two IGT variants suggesting that the frame of the variant has an effect on long-term decision making in the IGT (p < 0.001). The order in which a variant was presented, and the type of the instructions that were used both had an effect on long-term decision making in the two IGT variants (p < 0.05). A post hoc test suggested that the instructions that differentiated between reward and punishment resulted in greater foresight than the commonly used IGT instructions that fail to distinguish between reward and punishment. As observed in previous studies, there were more number of participants (60%) who showed greater foresight in the punishment variant than in the reward variant (p< 0.001). The results suggest that foresight in IGT decision making is sensitive to reward and punishment frame in an asymmetric manner, an observation that is aligned with the behavioral decision-making framework. Benefits of integrating findings from behavioral studies in decision neuro